Insect Gut Microbiota and Their Role in Cellulose Degradation: A Brief Review - Maji, Poulami; Maji, Megha; Shukla, Prashant; Ghosh, Paramita (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Insects are most versatile organisms in animal kingdom. They are about to live in different environment and are successful in habiting most of the niches. The adaptability of insects are due to the enzymes they produce and the symbiotic relationship they have with microorganisms. Cellulose is the fibre which provides strength to plant cell. It is flexible and strong and higher animals are not able to digest it on their own. Some bacteria, fungi and protozoa produce cellulase which breaks down the cellulose chain into shorter fragments enabling them to utilize the molecules for their growth. Many such bacteria live in symbiotic relationship with insects which are herbivores or omnivores as generally insects do not produce cellulase of their own. There are certain insects which have developed the capacity to produce cellulases but their numbers is too less than those which do not produce those enzymes. The current review is an attempt to provide information about the insects who harbour bacteria in their guts and are able to degrade cellulose. This review explores the critical role of cellulose degrading bacteria in the insect gut, focusing on their symbiotic relationships and potential applications in biofuels, waste management, and industrial processes. Highlighting diverse insect species, this study discusses enzyme production, bacterial interactions, and industrial utilization.